A Linguistic Approach to the Speech Acts in Aljahez`s Discourse: The Example of Earthly Life and After life Treatise - Malek Yaseen; Malaz Harfosh (دراسات في اللغة العربيّة وآدابها)
The issue of speech act is a significant issue in pragmatics. Speech acts encapsulate lectionary, illocutionary and perloctionary forces. I have dealt with what is said in speech. What is said is an achieved action. To be achieved, this action depends on presuppositions or prior assumptions between the speaker and the recipient of speech. The speaker discusses his previous references to make his words an action which should be done. All of the above depends on the context. Although pragmatics is considered a western branch of knowledge and scholarship which has introduced the idea of speech act, our tradition is not devoid of similar ideas although they may have been expressed through other terms.In this research, we have tried to take a linguistic approach midway between western thinking and Arabic one and studying one of the most important linguistic and intellectual heritage resources to make our present linguistic knowledge base richer and reveal the depth our traditional knowledge.